Preferencias estéticas en los recorridos escolares : dibujos que dan voz - Alonso-Sanz, Amparo (2018)
From everyday aesthetic, we study preferences about educative environment of Spanish students (6 to 12 years old) from 3 schools of Alicante city. Through Visual Arts Based Research, it is possible to show visual average of the students’ itineraries at their schools. Finally, it is conclude with the aesthetic preferences, contempt and indifferences, between body and environment